1997
DOI: 10.1063/1.366121
|View full text |Cite
|
Sign up to set email alerts
|

Strain and defects depth distributions in undoped and boron-doped Si1−xGex layers grown by solid phase epitaxy

Abstract: Strain-conserving doping of a pseudomorphic metastable Ge0.06Si0.94 layer on Si(100) by low-dose BF2 + implantation A detailed characterization of undoped and heavily boron-doped Si 1Ϫx Ge x layers with xϭ0.21, 0.26, and 0.34 grown on ͑001͒ Si wafers by solid phase epitaxy is presented. The starting material for solid phase epitaxial growth was prepared by amorphization of epitaxial SiGe-Si heterostructures by ion implantation. In order to obtain doped layers, boron was also implanted into some of the amorphou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…8 The parameters used to characterize the strain in the layers are the lattice misfit (f) between the bulk lattice constants of layer and substrate, which depends on the Ge content of the layers, and the normalized strain of each slice (∑), which gives the fraction of the strain for coherency on the silicon substrate. This experimental procedure is described elsewhere in detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The parameters used to characterize the strain in the layers are the lattice misfit (f) between the bulk lattice constants of layer and substrate, which depends on the Ge content of the layers, and the normalized strain of each slice (∑), which gives the fraction of the strain for coherency on the silicon substrate. This experimental procedure is described elsewhere in detail.…”
Section: Methodsmentioning
confidence: 99%
“…11 Knowledge of the values of the phonon frequencies allows the inversion of Eq. 4,5,8,9 Figure 1b shows the HREM image of the sample with x = 0.26 grown at 800°C. (2) and thus the determination of the Ge fraction and a value of the normalized strain representative of the whole epitaxial layer.…”
Section: Methodsmentioning
confidence: 99%
“…This is believed to be due to the lower effective mass of holes in Si Ge which could account for a 20% enhancement and probably the existence of biaxial compressive strain in the channel which lifts the degeneracy of the light-hole (LH) and heavy-hole (HH) bands at the point, leading to an even lower in-plane effective mass of the topmost HH band [4], [5]. The strain and defects depth profile of SPE grown SiGe layers on (100) Si has been studied in [21]. In that work, it was found that a fully-strained defect-free 30-nm thick Si Ge layer can be grown by SPE if it is heavily boron-doped.…”
Section: A Performance Enhancement From Sige Heterostructure Channelmentioning
confidence: 99%
“…In that work, it was found that a fully-strained defect-free 30-nm thick Si Ge layer can be grown by SPE if it is heavily boron-doped. Undoped samples are 80% strained, i.e., partially relaxed, for the same Ge composition [21]. In our SiGe-channel device considered here, the SPE first proceeds vertically from the heavily doped source region, in which full compressive strain is believed to exist in the graded SiGe layer.…”
Section: A Performance Enhancement From Sige Heterostructure Channelmentioning
confidence: 99%
“…In the previous reports, great efforts have been expended on the elimination of MDs in p + /p and p/p + epiwafers. Masazara [2], Herzog [3], Lee [4], Tillack [5], Rodriguez [6] presented Ge-B codoping in epi-layers to reduce the mismatch strain in the p + /p epi-wafers. Lin [7] pointed out that mismatch strain in the p/p + epi-wafers could be reduced by Ge-B codoping in the heavily borondoped substrates, thereby, the warpage and bow of epiwafers could be reduced.…”
Section: Introductionmentioning
confidence: 99%